Pengaruh Progressive Muscle Relaxation terhadap Kualitas Tidur dan Kelelahan dalam Kegiatan Perkuliahan pada Mahasiswa Jurusan Okupasi Terapi Poltekkes Kemenkes Surakarta - Rina Kurnia; Lis Sarwi Hastuti (Politeknik Kesehatan Kemenkes Surakarta, 2023)
Abstract Background. Learning or lecturing is a process of interaction between instructors/teachers/lecturers and students. To obtain better learning outcomes, the learning approach used by lecturers influences students' activities and learning outcomes. The lecture process which involves physical and mental activity can cause learning fatigue and poor sleep quality. One effort that can be made to reduce study fatigue and improve student sleep quality is by providing progressive muscle relaxation (PMR) regularly. Objective. This study aims to determine the effect of PMR on sleep quality and fatigue during lecture activities among students majoring in Occupational Therapy, Health Polytechnic, Ministry of Health, Surakarta. Method. The design of this research is quasi experimental